1989
DOI: 10.1002/jbm.820231406
|View full text |Cite
|
Sign up to set email alerts
|

Toxic hydrolysis product from a biodegradable foam implant

Abstract: A commercially available mammary implant containing a soft polyester polyurethane foam shell has been examined for possible diamine hydrolysis products. Fourier Transform Infrared (FT-IR) analysis has shown ester and aromatic structures present in the intact foam shell. Vigorous hydrolysis conditions using NaOH have produced a mixture with large amounts of toluene diamine (TDA) present as determined by Gas Chromatography-Mass Spectrometry (GC/MS), and GC/FT-IR. There are numerous clinical reports of the degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…One of the degradation products of TDI is 2,4-toluenediamine (2,4-TDA). Data in experimental animals showed that the PU foam cover degraded within [6][7][8][9][10][11][12] months of implantation (2). This result was consistent with the clinical observations in patients with Meme breast implants (3,4).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…One of the degradation products of TDI is 2,4-toluenediamine (2,4-TDA). Data in experimental animals showed that the PU foam cover degraded within [6][7][8][9][10][11][12] months of implantation (2). This result was consistent with the clinical observations in patients with Meme breast implants (3,4).…”
supporting
confidence: 80%
“…Our own in vitro studies indicated that 2,4-TDA was slowly released over time by hydrolytic degradation when PU foam samples were incubated under mild physiological conditions (5,6). The amount and rate of 2,4-TDA production observed in vitro varied with the conditions of PU foam exposure (7)(8)(9). The carcinogenicity of 2,4-TDA was studied extensively in mice, rats, and other species (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…These aromatic diisocyanates can be converted into aromatic diamines that are toxic and potentially carcinogenic to humans. 20,21 In clinical practice durable PUs degrade very slowly, and the risk of a toxic effect is negligible. 19,22 However, with biodegradable PUs the risk of relevant levels of toxic degradation products is higher.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1980s, there was concern that a relationship between the components derived from the degradation of polyurethane (especially 2,4 toluenediamine [TDA]) and breast cancer could exist [4]. This relation has since been disproved by many studies [18,32] including reports from the Food and Drug Administration (FDA) [18,32] stating the conclusion that the polyurethane foam is safe, that the concentration of TDA in the urine of patients with polyurethane-covered implants is minimal, and that no statistical difference in TDA concentration was found between patients with polyurethane-covered implants and a control group [16].…”
mentioning
confidence: 99%